2019
DOI: 10.3390/pharmaceutics11110603
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Compression Matrix Made from Xanthan Gum and Low Molecular Weight Chitosan Designed to Improve Compressibility in Controlled Release Tablets

Abstract: The subject of our research is the optimization of direct compression (DC), controlled release drug matrices comprising chitosan/xanthan gum. The foregoing is considered from two main perspectives; the use of low molecular weight chitosan (LCS) with xanthan gum (XG) and the determination of important attributes for direct compression of the mixtures of the two polymers. Powder flow, deformation behaviour, and work of compression parameters were used to characterize powder and tableting properties. Compression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…P k , which represents the pressure needed to reduce (a) into half its initial value, is the most important Kawakita parameter to be tested. This is due to the fact that it represents how hard the granules are, and therefore, their ability to be used in direct compression applications [27]. The data in Figure 6 shows that the P k values of compacted raw chitin powder were the highest amongst all three types of samples.…”
Section: Kawakita Compression Analysismentioning
confidence: 99%
“…P k , which represents the pressure needed to reduce (a) into half its initial value, is the most important Kawakita parameter to be tested. This is due to the fact that it represents how hard the granules are, and therefore, their ability to be used in direct compression applications [27]. The data in Figure 6 shows that the P k values of compacted raw chitin powder were the highest amongst all three types of samples.…”
Section: Kawakita Compression Analysismentioning
confidence: 99%
“…However, in general, most direct compression and granulation processes would be considered to be particulate level blends given the size of their constituent particles. A relevant example from the recent literature describes the use of 90-250 μm particle size range chitosan and xanthan gum blends for use as a direct compression matrix [69]. In this case, the polymer blend is clearly at the particulate level given its particle size range and the use of a direct compression process which does not involve size reduction of the powders.…”
Section: Particulate Level Blendsmentioning
confidence: 99%
“…Natural anionic polymers have been extensively used for the development of PECs [ 5 , 6 , 7 , 8 ]. However, anionic cellulose derivatives such as hypromellose phthalate [ 4 ] and carboxymethyl cellulose sodium [ 9 ] show greater control of the molecular weight and the number of carboxylic groups (COO − ).…”
Section: Introductionmentioning
confidence: 99%
“…The degree of substitution, which is determined by the number of carboxymethyl groups per unit of CMC, has been widely studied and is one of the main factors affecting its physicochemical behavior [ 9 , 10 ]. Recent studies have shown that the development of matrix tablets containing mixtures of CS and anionic polymers self-assemble during the compression process [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%